How to speak money : - Velshi, Ali (Wiley, 2012)
The book will: * Shed light on the male and female spending and investing disparity * Discuss emerging international economies * Weigh the financial hurdle of student debt culminating in a successful job * Explain how to budget wisely and build wealth * Show how to plan appropriately for retirement How to Speak Money is an easy-to-read, practical book that helps readers become fluent in the world s most universal language.